2005
DOI: 10.1111/j.1365-2826.2005.01365.x
|View full text |Cite
|
Sign up to set email alerts
|

Formalin Attenuates the Stress‐Induced Increase in Plasma Epinephrine Levels

Abstract: Subcutaneous (s.c.) injection of formalin into rats is frequently used as a painful stressor that produces a three-phase nociceptive response. We have shown previously that s.c. administered formalin (0.2 ml of 4% solution per 100 g body weight) unexpectedly attenuated the increase of plasma epinephrine levels in rats exposed to exteroceptive stressors (handling, immobilisation). To clarify the mechanism(s) responsible for this phenomenon, the effect of formalin applications on epinephrine plasma levels was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Immobilization also elicits an increase in plasma PRL levels with peak levels between 10 and 20 min [31, 32]. Previously, we have reported a sudden and strong reduction of plasma epinephrine levels in immobilized animal whether they were injected with formalin before or during immobilization [13, 14]. Our present results show that the administration of formalin cannot produce any further changes in hypothalamo-pituitary-adrenocortical (HPA) activity of immobilized rats (fig.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Immobilization also elicits an increase in plasma PRL levels with peak levels between 10 and 20 min [31, 32]. Previously, we have reported a sudden and strong reduction of plasma epinephrine levels in immobilized animal whether they were injected with formalin before or during immobilization [13, 14]. Our present results show that the administration of formalin cannot produce any further changes in hypothalamo-pituitary-adrenocortical (HPA) activity of immobilized rats (fig.…”
Section: Discussionsupporting
confidence: 46%
“…a significant increase in plasma norepinephrine (NE) levels, while change of plasma epinephrine (EPI) level is largely dependent on the concentration and the mode of application of the formalin solution [11, 12]. Our group has recently found that a single subcutaneous injection of formalin (0.2 ml of 4% solution/100 g BW) into the hind limb is able to attenuate the immobilization-induced increase of plasma catecholamines [13, 14]. …”
Section: Introductionmentioning
confidence: 99%
“…These observations are consistent with our previous reports showing that subcutaneous injection of 0.2 ml/100 g b.w. of 4% formalin attenuates stress-induced elevations of EPI in the plasma during first 15-30 minutes after application (Mravec et al 2004(Mravec et al , 2005. Formalin acts on EPI and NE levels in both sham-operated and transected rats.…”
Section: Discussionmentioning
confidence: 99%
“…Subcutaneous applications of formalin elicit pain behavioral responses (Abbott et al 1995), increase the blood pressure and heart rate (Culman et al 1997), and elevate the levels of NE, ACTH, corticosterone and prolactin in the plasma (Kant et al 1982;Pacak et al 1998;Vissers et al 2004). However, epinephrine secretion depends on the concentration and the volume of applied formalin solution (Culman et al 1997;Pacak et al 1998;Mravec et al 2004;Mravec et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation